Clássicos da literatura infantil sob o olhar do ensino de ciências: uma proposta para os anos iniciais - Breunig, Eduarda Tais (2021)
Scientific literacy in the early years is extremely important, as it helps students to better understand the world in which they live. A possible means of its insertion in the early years is in children's literature, which can contribute a lot of scientific knowledge, through a simple story. The aim of this research was to investigate and analyze the stereotyped representations about characters in children's literature stories and from these, promote scientific literacy through classic literature stories. The qualitative study was guided by the focus of exploratory research (case study) and by the categorization proposed by Bardin. As a methodology, we used a didactic sequence divided into two different moments, since we were unable to apply the entire planned sequence in the early years, due to the Covid-19 pandemic. With this, we apply in the classroom the initial part of the sequence with the initial years, in which we investigate the participants' previous conceptions. The steps of the didactic sequence were: 1) Application of the previous questionnaire to analyze the participants' conceptions; 2) A counting circle shared by the students of the stories of Chapeuzinho Vermelho and Três Porquinhos, followed by a conversation circle. The rest of our thematic didactic sequence about the maned wolf and the peccary pig was applied as a proposal to a group of students from the normal course, remotely by google met, which included the following steps: 1) Previous questionnaire; 2) Presentation of this research project; 3) Presentation of thematic didactic sequence, with activities about the maned wolf and the peccary pig; 4) Final questionnaire to validate the thematic didactic sequence. The results found in the intervention carried out with the early years showed that children in general have conceptions related to the wolf character and the three little pigs, strongly influenced by the tales of Little Red Riding Hood and Three Little Pigs. The wolf character is remembered for his reputation as a villain by most children, while the three little pigs are seen as good by all children. Some children make no distinction between the fictional world and the real world, and end up characterizing all wolves as villains, both the wolf character and the real-life wolf. This negative characterization of the wolf is also attributed to the fact that most children believe that it is a carnivore, and can even eat people. However, other children recognize that the wolf is only carnivorous because of its animal instincts, and that doesn't make it bad. Some results found in the conversation circle were also discussed based on the scientific literacy indicators proposed by the authors Sasseron and Carvalho. The results referring to the second stage of the research, applied in the normal course, showed that some participants are already able to perceive some stereotypes present in children's literature, but that many had never thought of working science associated with children's literature. However, after this acquired knowledge, they intend to work, as they recognize the importance of working with Brazilian native animals with children, and science in general. Thus, we realize that these fragmented and stereotyped views that may be developed through a fairy tale must be worked on in the classroom, under the teacher's mediation, in order to get around them. A possible alternative is to promote scientific literacy through classic children's tales, which was portrayed in the rewritten versions of the Little Red Riding Hood and the Three Little Pigs, the maned wolf (Chrysocyon brachyurus) and the peccary pig (Pecari tajacu) as characters, which are present in our Brazilian fauna, and can act as important allies in promoting scientific literacy. Furthermore, all the other activities proposed in the thematic didactic sequence tend to collaborate even more in the knowledge related to these animals.